Bacterial virulence factors and rho GTPases - Boquet, Patrice. (Current topics in microbiology and immunology,, 2005)
Pathogenic bacteria for human and animals have developed sophisticated weapons, termed virulence factors, to ensure their replication and persistence into their hosts. The first role of these virulence factors is to loosen the host defenses against microorganisms represented by innate and adaptive immunities. Small GTPases of the Rho subfamily have been shown top play important functions in theses systems. The authors of this volume present the synthesis on how the various host cellular rho GTPases activities are manipulated by bacteria to fulfill their virulence. Bacterial virulence strategies that utilize rho GTPases -- Extracellular bacterial pathogens and small GTPases of the rho family: an unexpected combination -- Triggered phagocytosis by salmonella: bacterial molecular mimicry of rho GTPase activation/deactivation -- Regulation of phagocytosis by rho GTPases -- The immunological synapse and rho GTPases -- Rho GTPases and the control of the oxidative burst in polymorphonuclear leukocytes -- Clostridial rho-inhibiting protein toxins -- The type III cytotoxins of yersinia and pseudomonas aeruginosa that modulate the actin cytoskeleton -- Modulation of rho GTPases and the actin cytoskeleton by YopT of yersinia -- Bacterial toxins activating rho GTPases.